The indefinable concept of terrorism - Fletcher, George P. (Journal of international criminal justice, 2006)
As the concept of terrorism fulfils multiple functions, the better way to think of terrorism is not as a crime but as a different dimension of crime, a higher, more dangerous version of crime, a kind of super-crime incorporating some of the characteristics of warfare. There are at least eight primary factors that bear on terrorism: the factor of violence; the required intention; the nature of the victims; the connection of the offender to the state; the justice and motive of their cause; the level of organization; the element of theatre; and the absence of guilt. However, one cannot draw from these variables a simple (or indeed even a complex) definition of terrorism. The reason is that not all the factors apply all the time. Any proposed definition produces counterexamples. The way to think about terrorism is, therefore, to become aware of all the relevant factors but not to expect that they will all be fulfilled in any particular case. The specific cases of terrorism are related the way the members of a family are related. Most, but not all, might have the same eye shape. Others might have hair colour or the shape of their nose in common; still others might be tall or short. One should try to picture a series of overlapping sets in which no set intersects with all the others. That is the way our intuitions of terrorism operate